Prefrontal Cortex and Amygdala Subregion Morphology Are Associated With Obesity and Dietary Self-control in Children and Adolescents - Kim, Mimi S.; Luo, Shan; Azad, Anisa; Campbell, Claire E.; Felix, Kimberly; Cabeen, Ryan P.; Belcher, Britni R.; Kim, Robert; Serrano-Gonzalez, Monica; Herting, Megan M. (Frontiers in Human Neuroscience, 2020)
A prefrontal control system that is less mature than the limbic reward system in adolescence is thought to impede self-regulatory abilities, which could contribute to poor dietary choices and obesity. We therefore aimed to examine whether structural morphology of the prefrontal cortex (PFC; involved in cognitive control) and the amygdala (a key brain region for reward related processing) are associated with dietary decisions and obesity in children and adolescents. Seventy-one individuals between the ages of 8-22 years (17.35 ± 4.76 years, 51% female, 56% with overweight or obesity) participated in this study; each participant completed a computer-based food choice task and a T1- and T2-weighted structural brain scans. Two indices of obesity were assessed, including age and sex-specific body mass index (BMIz) and waist-to-height ratio (WHtR). The behavioral task included rating 60 food stimuli for tastiness, healthiness and liking. Based on each participant’s own ratings, 100 binary food choices were then made utilizing a computer mouse. Dietary ‘self-control’ was calculated as the proportion of trials where the individual chose the healthier food item (versus the tastier food item) over the total number of trials. Cortical thickness and amygdala subnuclei volumes were quantified using FreeSurfer 6.0 and CIT168 atlas respectively. We found that WHtR was negatively associated with thickness of bilateral superior frontal, left superior temporal, right insula, and right inferior temporal regions (p < 0.05, corrected for multiple comparisons). We also found WHtR to be positively associated with volume of central nucleus (CEN) region of the amygdala (p = 0.006), after adjusting for hemisphere, age, sex, and intracranial volumes. Similar data pattern was observed when BMIz was used. Moreover, we found that across all participants, thinner right superior frontal cortex and larger left CEN volumes predicted lower dietary self-control. These results suggest that differential development of the PFC and amygdala relate to obesity and dietary self-control. Further longitudinal studies are merited to determine causal relationships among altered PFC to amygdala neural circuitry, dietary self-control, and obesity.